2007
DOI: 10.1074/jbc.m610341200
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Effect of Zn2+ in Native Bovine Rhodopsin

Abstract: Single-molecule force spectroscopy (SMFS) is a powerful tool to dissect molecular interactions that govern the stability and function of proteins. We applied SMFS to understand the effect of Zn 2؉ on the molecular interactions underlying the structure of rhodopsin. Force-distance curves obtained from SMFS assays revealed the strength and location of molecular interactions that stabilize structural segments within this receptor. The inclusion of ZnCl 2 in SMFS assay buffer increased the stability of most struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 56 publications
3
66
2
Order By: Relevance
“…This assay is based on the heat quantity necessary to promote the cis→all trans isomerization process of the retinal chromophore as a consequence of interhelical movements resulting from temperature increase. Recently, a stabilizing effect was reported for zinc ions on Rho in membranes immobilized on a surface [56]. The apparent discrepancy between our results and the ones from the single-molecule force spectroscopy study [56] can be explained if we take into account that our thermal bleaching kinetics determined in detergent solution may be also reflecting a specific effect of the zinc chloride salt used in the experiment on the heat conductivity of the solution.…”
Section: Transfer Modelcontrasting
confidence: 90%
See 2 more Smart Citations
“…This assay is based on the heat quantity necessary to promote the cis→all trans isomerization process of the retinal chromophore as a consequence of interhelical movements resulting from temperature increase. Recently, a stabilizing effect was reported for zinc ions on Rho in membranes immobilized on a surface [56]. The apparent discrepancy between our results and the ones from the single-molecule force spectroscopy study [56] can be explained if we take into account that our thermal bleaching kinetics determined in detergent solution may be also reflecting a specific effect of the zinc chloride salt used in the experiment on the heat conductivity of the solution.…”
Section: Transfer Modelcontrasting
confidence: 90%
“…Recently, a stabilizing effect was reported for zinc ions on Rho in membranes immobilized on a surface [56]. The apparent discrepancy between our results and the ones from the single-molecule force spectroscopy study [56] can be explained if we take into account that our thermal bleaching kinetics determined in detergent solution may be also reflecting a specific effect of the zinc chloride salt used in the experiment on the heat conductivity of the solution. Therefore, our thermal bleaching results suggest zinc specific effects on the structure of the receptor by measuring the hydrolysis of the chromophore from the protein.…”
Section: Transfer Modelcontrasting
confidence: 90%
See 1 more Smart Citation
“…Since each unfolding step has a certain probability to be taken, this is also the case for the unfolding pathway. 9 Experiments on bacteriorhodopsin (BR), 10,11 NhaA 12 and bovine rhodopsin 13,14 have shown that small changes in the environment can alter interactions stabilizing the structural segments within membrane proteins. We have recently shown that inter-and intramolecular interactions contribute differently towards stabilizing these structural segments.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the kinetic response of the individual structural elements by dynamic SMFS (DFS) allows quantification of their unfolding free energy, kinetic stability, conformational variability, and mechanical flexibility (33). Both SMFS and DFS have been applied to characterize these parameters of various membrane proteins and follow how they change on changing their functional state or physiological environment (34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%